DIFFICULTIES AND WAYS TO OVERCOME THEM IN THE PROCESS STUDYING A FOREIGN LANGUAGE IN SECONDARY SPECIAL EDUCATIONAL INSTITUTION (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the problem of determining any difficulties and ways of their overcoming in the process of a foreign language learning in a secondary specialized educational establishment.